Size-fractionated microbiome observed during an eight-month long sampling in Jiaozhou Bay and the Yellow Sea - Jianchang Tao; Wenxiu Wang; J L Weissman; Yongyu Zhang; Songze Chen; Yuanqing Zhu; Chuanlun Zhang; Shengwei Hou (Scientific Data, 2022)
Measurement(s) temperature of seawater • salinity of seawater • chlorophyll a • particulate organic carbon (POC) of seawater • dissolved organic carbon (DOC) of seawater • total nitrogen (TN) of seawater • total nitrate of seawater • nitrite of seawater • Phosphate of seawater • Silicate of seawater • Ammonium of seawater Technology Type(s) CTD sampler (Sea-Bird) • Shimadzu TOC-VCPH analyzer • Shimadzu TOC-L Analyzer • SEAL AutoAnalyzer 3 automatic continuous flow analyzer Factor Type(s)  geographic location • temporal instant Sample Characteristic - Organism marine metagenome Sample Characteristic - Environment marine seawater Sample Characteristic - Location Jiaozhou Bay